Analisis SWOT Strategi Pemasaran Produk Pada Pegadaian Syariah Hasanuddin Unit Soreang - Nur Indah Sari (AT TAWAZUN: Jurnal Ekonomi Islam, 2025)
This research is motivated by sharp business competition which is a challenge for entrepreneurs to remain competitive in their business results, especially in pawnshop products. The purpose of this research is to determine product marketing strategies and SWOT analysis of marketing strategies at the Hasanuddin Syariah Pegadaian Soreang Unit. The method used is SWOT analysis and descriptive analysis using qualitative research. The results of this research are based on the marketing mix according to Philip Kotler and Garry Armstrong who define the marketing mix as a set of marketing variables that can be controlled and combined to produce the desired response in the target market. The results of research using the SWOT analysis method of internal factors and internal factors show that the company has strengths from its internal factors and has good opportunities from its external factors. The next alternative marketing strategy is aggressive, which means that the Soreang Syariah Hasanuddin Unit pawn shop is in a very favorable condition so that it can continue to expand and achieve maximum progress.Keywords: Strategy, marketing, SWOT analysis